Study on Headline Earnings Reporting and It’s Value Relevance in Listed Companies in Tehran Stock Exchange - Mehdi Baharmoghadam (Shahid Bahonar University of Kerman, 2016)
In this paper, headline earnings reporting and it’s value relevance components have been studied, using data from companies listed in the Tehran Stock Exchange (TSE). To test the relative and incremental value relevance, regressions for price and return levels within Ohlson (1995) model were used.The data from a sample of 72 companies listed in the TSE, in the period 2003 to 2014, was used. The results of price levels regression showed that the headline earnings, in contrary to the headline earnings exclusions, have incremental value relevance. Also, the results of return levels regression, indicated that the headline earnings, in contrary to headline earnings exclusions, lack incremental value relevance. For relative value relevance, the test results of Vuong (1989) in price levels regression showed that the headline earnings have not relative value relevance more than basic earnings. This test in return levels regression showed that the headline earnings have relative value relevance more than basic earnings.